PENGARUH CAPITAL ADEQUACY RATIO, NON PERFOMING FINANCING, FINANCING TO DEPOSIT RATIO, BIAYA OPERASIONAL, DAN PENDAPATAN OPERASIONAL, DAN UKURAN PERUSAHAAN TERHADAP RETURN ON ASSET BANK UMUM SYARIAH DI INDONESIA - Edi Wibowo, Nunung Indrawati, Suprihatmi Sri Wardiningsih & (Universitas Slamet Riyadi, 2018)
This research is meant to find out the influence of the variables of Capital Adequacy Ratio (CAR), Non Perfoming Ratio (NPF), Financing to Deposit Ratio (FDR), (BOPO) dan Firm size to Return on Asset of Islamic banks operating in Indonesia from 2014 – 2016. The sample collection technique has been carried out by using purposive sampling method with the criteria of Islamic banks makes an annual financial report in the period 2014 – 2016, has been published in Islamic banks and banking companies have profit in the period 2014 – 2016. Based on the predetermined criteria, the sample of 6 Sharia Commercial Banks is obtained. The type of data used in this study is secondary data using financial report data and analysis techniques used are multiple linear regression. Result of t test show CAR, NPF, FDR and Company Size have no significant effect to ROA, but BOPO show significant influence to ROA. The result of F test of CAR, NPF, FDR, BOPO and Firm Size ratio have significant effect to ROA.Keywords: CAR, NPF, FDR, BOPO, Firm Size, ROA